2022
DOI: 10.1183/16000617.0042-2022
|View full text |Cite
|
Sign up to set email alerts
|

Does pulmonary rehabilitation address treatable traits? A systematic review

Abstract: BackgroundThere is growing interest in a “treatable traits” approach to pulmonary rehabilitation in chronic airways disease. The frequency with which pulmonary rehabilitation programmes address treatable traits is unknown.MethodsRandomised controlled trials of pulmonary rehabilitation compared to usual care in patients with stable chronic airways disease were included. The components of pulmonary rehabilitation delivered were extracted and mapped to treatable traits in pulmonary, extrapulmonary and behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Treatable traits is a precision-medicine model of care that involves identifying traits using a multi-dimensional assessment in an individual and creating a personalised management strategy that targets these traits 10 .This approach to patient care has been shown to be effective in people with OAD 10,30 , and treatable traits has been proposed to optimise pulmonary rehabilitation outcomes. Our study suggests that people who 'can't do, don't do' may benefit from pulmonary rehabilitation most, where additional traits can be targeted to improve physical capacity and physical inactivity 31 .…”
Section: Discussionmentioning
confidence: 87%
“…Treatable traits is a precision-medicine model of care that involves identifying traits using a multi-dimensional assessment in an individual and creating a personalised management strategy that targets these traits 10 .This approach to patient care has been shown to be effective in people with OAD 10,30 , and treatable traits has been proposed to optimise pulmonary rehabilitation outcomes. Our study suggests that people who 'can't do, don't do' may benefit from pulmonary rehabilitation most, where additional traits can be targeted to improve physical capacity and physical inactivity 31 .…”
Section: Discussionmentioning
confidence: 87%
“…A recent systematic review, however, highlighted that, while deconditioning was addressed in almost all the randomised controlled studies on pulmonary rehabilitation, other treatable traits were addressed much less frequently ( e.g. obesity/cachexia in 18% of studies, anxiety/depression in 10% of studies and encouragement to engage independently in exercise only in 46% of reported studies) [ 17 ]. Nevertheless, these traits are very prevalent in individuals with COPD.…”
Section: Definition Of (Modern) Pulmonary Rehabilitationmentioning
confidence: 99%
“…The extent to which pulmonary rehabilitation programmes currently address treatable traits is unclear. A recent systematic review evaluated 116 RCTs of pulmonary rehabilitation with 6893 participants to establish the frequency with which individual traits were addressed 65 . The trait of deconditioning was addressed in 97% of studies through the provision of exercise training.…”
Section: Different Models Of Carementioning
confidence: 99%
“…A recent systematic review evaluated 116 RCTs of pulmonary rehabilitation with 6893 participants to establish the frequency with which individual traits were addressed. 65 The trait of deconditioning was addressed in 97% of studies through the provision of exercise training. There was evidence that some extrapulmonary and behavioural/lifestyle traits were addressed in pulmonary rehabilitation, but this occurred in a relatively small number of studies.…”
Section: Treatable Traits In Pulmonary Rehabilitationmentioning
confidence: 99%